Comparative analysis of operational risk in Chinese and UK banking industries - Xie, Jingyi (2018)
This dissertation focuses mainly on banking operational risk measured by capital requirement. This empirical research estimates the macroeconomic variables and bank-specific characteristics of operational risk regulatory capital for the United Kingdom (UK hereafter) and China respectively. Methodologically, this dissertation selects panel data to undertake a regression analysis. The data sample was secondary data collected from Orbis Bank and World Bank over a period from 2011 to 2018. This empirical research found that the large scale of banks associated with high profitability, solvency, liquidity and better investment decision-making may need more operational risk regulatory capital in both the UK and China. This means they are more likely to be influenced by banking internal control. However, for macroeconomic factors, UK and Chinese banks are quite different. The unemployment rate may have a more significant impact on Chinese banks than UK banks. This implies that Chinese banks can control the unemployment rate to improve operational risk. For other macroeconomic variables, GDP growth and employee numbers have opposite effects on the UK and Chinese banking industry. Specifically, GDP growth is positively linked to UK banks but negatively linked to China. These research results emphasize the differences and similarities between the UK and Chinese banking market, as well as the impact of each determinant made in each country to promote operational risk management. This dissertation therefore summarizes the experience and drawbacks of both the UK and Chinese banking market to maintain a stable economy and financial development in the final section.